Pendampingan Anak dalam Mengenal dan Melestarikan Budaya Lokal melalui Komunitas Seni Karawitan Kabupaten Mojokerto - Ahmad Aly Syukron Aziz Al Mubarok; A Fandi Bastian (GUYUB: Journal of Community Engagement, 2024)
In the modern era, children's awareness of Karawitan culture, especially elementary school students, is decreasing because many foreign cultures have stepped foot in Indonesia. The children's interest in studying foreign cultures is much greater than studying their own culture. This is the basis for holding Karawitan mentoring activities at SDN Ngastemi 1 Bangsal and SDN Dukuhngarjo Jatirejo, Mojokerto Regency, to stimulate and encourage students' awareness of local culture, particularly in Karawitan. The method used in this community engagement was Participatory Action Research (PAR). The data were obtained from several steps, namely visiting the village elders, introducing gamelan notation and its way, and training for gamelan. After participating in this community engagement, the children received support from teachers, parents and the surrounding community in caring for and preserving local culture.